(untitled) (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2023)
In contemporary understanding, a now normalized immersion continues to be associated with digitality and high-tech apparatuses, but is also seen as diffused into the lifeworld. Against this backdrop, the article focuses on two current artworks that extend the internal environmentality inherent in VR as a spatialized image into physical space by using strategies from installation and site-related art. These examples provide for an equation and nesting of work, environment and exhibition that is interpreted here as a potentiated environmentalization. The artistic VR-environments by no means negate their rootedness in imagery, but rather self-reflexively reveal the transitions between image and three-dimensionality, what gives them a special epistemic valence. It thus seems worthwhile to relate them to considerations of knowledge objects and exhibitions, but also to (queer) phenomenological theories of entanglement and becoming originating from the following of lines. Meanwhile, the epistemic value of their latent objects, disoriented paths, and impossible spaces is only revealed in the interaction with and embodied experience of the virtual space. The article thus participates in debates on how bodily immersion does not exclude, but enables action and reflection within aesthetic experience. With regard to two fundamental paradigms of immersion, it can show how, for this purpose, the artworks turn anew the strategies of de-distancing and de-differentiation.